The Most Favorable Rule: Its Determination - Pasco Cosmópolis, Mario (2004)
The application of the most favourable rule or regime in labour law is not as simple as its name suggests. Different rules, criteria and assumptions have to be assessed in each case, which makes it difficult to find the most favourable rule. In this sense, this paper offers a guide to address and find an answer to this problem. However, the author argues that before determining what is to be understood by "more favourable rule", certain preliminary questions need to be clarified, such as (i) the hierarchy of norms, (ii) the imperative force of norms, (iii) the concurrence of norms, and (iv) the principle of the "minimum rule". Once all these points are understood, it will be possible to analyse their interrelationship and in this way to find the "operative mark" of the most favourable rule. In conclusion, although there is no infallible method or single way of determining the most favourable rule, the author argues that any method can be valid, but this will always depend on the legislation of each country and other factors that are analysed in detail in this work.